Exploring the gut–kidney axis: possible connection between gastrointestinal and renal disorders in dromedary camels - Tharwat, Mohamed; Elmoghazy, Hazem M. M.; Abdallah, Abdelmonem (Frontiers in Veterinary Science, 2025)
IntroductionGastrointestinal (GI) disorders and renal dysfunction are common and clinically significant conditions in dromedary camels (Camelus dromedarius). However, their interrelationship—representing the gut–renal axis—remains poorly understood. This study aimed to investigate the association between GI disorders and renal function in camels using biochemical, ultrasonographic, and causal modeling approaches.MethodsSeventy camels were examined, including 49 with GI disorders and 21 clinically healthy controls. Affected camels were categorized as Group 1 (intestinal obstruction, n = 22), Group 2 (GI impaction, n = 20), and Group 3 (chronic diarrhea, n = 7). Clinical evaluation, ultrasonography of the GI and urinary tracts, and biochemical analyses of serum blood urea nitrogen (BUN) and creatinine were performed. Simple linear regression was used to model associations between GI disorders and renal biomarkers. Directed acyclic graphs were applied to identify potential mediators—hematocrit, total protein, sodium, potassium, albumin, globulin, and phosphorus—and estimate total and direct effects.ResultsCompared with controls, camels in Groups 1–3 had significantly elevated BUN (2.2-, 1.9-, and 2.6-fold) and creatinine (2.4-, 2.7-, and 3.0-fold) concentrations. Adjustment for mediators produced minimal change, suggesting robust and independent associations between GI disorders and renal impairment. Ultrasonographic findings supported these results: intestinal obstruction showed distended loops with reduced motility; impaction exhibited hyperechogenic rumen contents; and chronic diarrhea was associated with mucosal thickening, increased peristalsis, and mesenteric lymphadenopathy.DiscussionGastrointestinal disorders in dromedary camels are strongly linked to renal dysfunction, as evidenced by consistent biochemical and ultrasonographic abnormalities. These findings highlight the clinical relevance of the gut–renal axis in camels and emphasize the importance of early recognition and management of GI disorders to prevent secondary renal complications.